Percutaneous Transluminal Mitral Commisuriotomy for Mitral Stenosis in Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Chandra Mani (Nepalese Heart Journal, 2016)
Mitral stenosis (MS) is almost invariably the result of long term complication of rheumatic fever. Based upon the nature and severity of MS, patients can be managed with medical treatment, percutaneous transvenous mitral commissurotomy (PTMC) or surgery. PTMC is proven to be simple, effective and safe; it is considered as treatment of choice in the management of MS. In Shahid Gangalal National Heart Centre, PTMC service started in 2001. First PTMC in the centre was done on 14th April 2001. Till June2016, 6023 PTMCs were done in the centre. Multiple studies evaluated the safety and efficacy of PTMC in different groups of patients. These studies clearly demonstrated the safety and effectiveness of PTMC in our centre. This article summarizes the historical development, current status and future perspectives of PTMC procedure at Shahid Gangalal National Heart Centre, a teritary care cardiac centre in Nepal. Nepalese Heart Journal 2016; 13(2): 15-17